INFLUENCE OF MINERAL FERTILIZERS ON THE CONTENT OF NUTRIENTS IN THE SOIL AND THE YIELD OF SUNFLOWER HYBRIDS OF DIFFERENT MATURITY GROUPS - Hanhur, V. V. (Scientific Progress & Innovations, 2021)
In agrarian production of Ukraine, the main oil-bearing crop is sunflower (Helianthus annuus L.), the vol-umes of gross seed production of which increase almost every year. However, this positive tendency has been achieved mainly due to expanding the sown areas, rather than a significant yield increase. Therefore, it is im-portant to deepen research aimed at increasing the productivity and improving crop quality. The aim of the study was to determine the effect of different fertilizer rates on soil nutrient content and the productivity of sun-flower hybrids of different maturity groups. During field experiment at Poltava State Agricultural Experimental Station named after M.I. Vavilov in 2018–2020, it has been found that during sunflower hybrids cultivation, the highest content of nitrogen, which is easily hydrolyzed, was observed at N40P60K60 combined mineral fertilizer application. A decrease in nitrogen content in the soil at applying the maximum dose of N60P80 fertilizer was observed relative to using low and medium doses. Most of labile phosphorus was contained in the arable soil layer while cultivating Oreol hybrid at the background N30P40, Cadet hybrid – N40P60K60, and Drive hybrid – N40P60. It has been found out that the highest potassium content in the soil was at applying N40P60K60, or it was higher, as compared with the variant without fertilizers for maturity groups of hybrids – 21.6; 36.0; 44.3 mg/kg of soil, respectively. According to the research results, it has been revealed that in Oreol hybrid the increase in seed yield after using mineral fertilizers, made 0.15–0.28 t/ha or 4.8–8.9 % in comparison with the control. The yield of Cadet and Drive hybrids at the background of fertilization was higher as compared with the variant without fertilizers by 0.25–0.30 t/ha or 7.9–9.5 % and 0.10–0.23 t/ha or 3.0–6.9 %, respectively. The early-maturing Oreol hybrid provided the maximum seed yield of 3.41 t/ha at applying N60P80. It has been registered that the mid-early Cadet hybrid reacted the least to various fertilization backgrounds. The difference between the experimental variants in terms of seed yield made only 0.02–0.05 t/ha. The highest seed yield of Drive hybrid – 3.58 t/ha was obtained against the background of N60P80.